Intraoperative support of patients with infective endocarditis complicated by acute heart failure - H.B. Koltunova (Медицина неотложных состояний)
Background. Infective endocarditis (IE) is associated with certain risks and complications that can be controlled only by surgery. There is a limited number of recommendations on the anesthetic management of patients with IE during cardiovascular surgery or in the postoperative period in the intensive care unit. The aim of the study: to determine the peculiarities of intraoperative anesthetic management in patients with IE complicated by acute heart failure (AHF). Materials and methods. The study included clinical data of 72 patients with IE complicated by preoperative AHF who underwent cardiac surgery at the State Institution “Amosov National Institute of Cardiovascular Surgery of the National Academy of Medical Sciences of Ukraine” from January 1, 2019, to December 30, 2022. The diagnosis of IE was made in accordance with the Duke criteria. All patients had NYHA class IV. Results. In the group with IE complicated by preoperative AHF, 72 patients (100.0 %) were brought into the operating room from the intensive care unit in a critical condition and underwent urgent surgery for vital signs. The oxygenation index at baseline was 196.9 (123.8–287.5). A severe degree of respiratory failure at the preoperative stage was observed in 25 % of patients with IE complicated by HF. Patients were characterized by a significant need to restore the volume of circulating blood: the median value of intraoperatively transfused red blood cell mass was 688 ml (470–1092). Assessment of the baseline level of C-reactive protein revealed a median of 52.61 ng/ml (22.94–109.31). At the stage of completion of the surgical intervention, the content of C-reactive protein was 69.33 ng/ml (45.89–120.64). Multicomponent (administration of dobutamine and norepinephrine) support of the cardiovascular system was recorded in 42 (58.3 %) patients with IE complicated by preoperative AHF. Single-component support included the isolated use of one of the drugs in 30 (41.7 %) cases. Conclusions. The study highlights the main issues that anesthesiologists face during cardiac surgeries with bypass in these patients. The limited number of recommendations for the intraoperative management of patients with IE complicated by preoperative AHF encourages further research.